Impact of the 'reserved therapeutic space' nursing intervention on patient health outcomes: An intervention study in acute mental health units - Antonio R. Moreno‐Poyato; Khadija El Abidi; Teresa Lluch‐Canut; Montserrat Cañabate‐Ros; Montserrat Puig‐Llobet; Juan F. Roldán‐Merino (Wiley, 2023)
Abstract Aims To evaluate the effectiveness of the 'reserved therapeutic space' intervention for improving the nurse-patient therapeutic relationship in acute mental health units in Spain. Design Multicentre intervention study with control group. Methods The study will be carried out in 12 mental health units. The 'reserved therapeutic space' intervention to be tested has been co‐designed and validated by both nurses and patients. The quality of the therapeutic relationship, the care received and perceived coercion among patients will be assessed. An estimated 131 patients per group are expected to participate. Funding was granted by the Instituto de Salud Carlos III. Co‐financed by the European Union (European Regional Development Fund (ERDF) (PI21/00605)) and College of Nurses of Barcelona (PR‐487/2021). The proposal was approved by all the Research Ethics Committees of participating centres. Results This project will lead to changes in clinical practice, transforming the current models of organization and care management in mental health hospitalization units. No patient or public contribution.